2008
DOI: 10.1111/j.1530-0277.2007.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Where, With Whom, and How Much Alcohol Is Consumed on Drinking Events Involving Aggression? Event‐Level Associations in a Canadian National Survey of University Students

Abstract: These results support experimental evidence indicating a direct role of alcohol in aggression and point to characteristics of the drinking context that might be targeted in future prevention initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 71 publications
(95 reference statements)
5
43
0
1
Order By: Relevance
“…Alcohol use has consistently been related to intimate partner violence among adults and married couples (for a review, see Foran & O'Leary, 2008;Leonard & Quigley, 1999;Wells et al, 2008). Although less research has been conducted on the link between alcohol use and dating violence among college-aged individuals, a growing body of literature suggests that there is a signifi cant association (Fossos et al, 2007;Hines & Straus, 2007;Rapoza & Baker, 2008;Stappenbeck & Fromme, 2010, 2014Stets & Henderson, 1991).…”
Section: Alcohol and Dating Violencementioning
confidence: 99%
“…Alcohol use has consistently been related to intimate partner violence among adults and married couples (for a review, see Foran & O'Leary, 2008;Leonard & Quigley, 1999;Wells et al, 2008). Although less research has been conducted on the link between alcohol use and dating violence among college-aged individuals, a growing body of literature suggests that there is a signifi cant association (Fossos et al, 2007;Hines & Straus, 2007;Rapoza & Baker, 2008;Stappenbeck & Fromme, 2010, 2014Stets & Henderson, 1991).…”
Section: Alcohol and Dating Violencementioning
confidence: 99%
“…showed that the location where drinking occurs also accounts for a substantial part of alcohol-related harm (Bersamin, Paschall, Saltz, & Zamboanga, 2011;Casswell, Zhang, & Wyllie, 1993;Mihic, Wells, Graham, Tremblay, & Demers, 2009;Nyaronga, Greenfield, & McDaniel, 2009;Rossow, 1996;Single & Wortley, 1993;Stockwell, Somerford, & Ernie, 1992;Stockwell, Lang, & Rydon, 1993;Treno, Alaniz, & Gruenewald, 2000;Usdan, Moore, Schumacher, & Talbott, 2005;Walker, Waiters, Grube, & Chen, 2005;Wells, Graham, Speechley, & Koval, 2005;Wells, Mihic, Tremblay, Graham, & Demers, 2008). However, these studies were limited to crosssectional design and most of them were conducted in North America and Oceania.…”
mentioning
confidence: 92%
“…Substance use and mental health problems are both commonly associated with violence, including perpetration and victimization as well as partner violence and non-partner violence [e.g., 12,15,[24][25][26]. A substantial proportion of violent episodes involve use of alcohol and other drugs [26].…”
Section: Research On the Co-occurrence Of Mental Health Addiction Anmentioning
confidence: 99%
“…Empirical research indicates that mental health and addiction (MHA) disorders commonly co-occur [1,3], and that these disorders, as well as their co-occurrence, are strongly associated with violence [7][8][9][10][11][12][13][14][15]. Mental health problems, addictions, and violence (abbreviated in the present paper as MHAV) have complex aetiologies involving both individual-level factors (including socio-demographic, biological, and psycho-social variables) as well as community/environmental-level influences (such as levels of neighborhood disorganization and unemployment rates) that may have independent and interactive effects.…”
Section: Introductionmentioning
confidence: 99%